Interview with Andrew Erskine: government, ideology and Hellenization in the Hellenistic World - Erskine, Andrew (Romanitas - Revista de Estudos Grecolatinos, 2016)
Interview with Andrew Erskine.
Keywords: Interview; Andrew Erskine; Hellenistic World